Genomic epidemiological characteristics of dengue fever in Guangdong province, China from 2013 to 2017. - Bangyao Sun; Xin Zhang; Huan Zhang; Haizhou Liu; Lina Sun; Qiqi Tan; Mifang Liang; De Wu; Di Liu (Public Library of Science (PLoS), 2020)
Dengue fever, a mosquito-borne viral disease in humans, has been endemic in many Southeast Asian countries. Since its first outbreak in 1978 in Foshan, Guangdong province, China, dengue has been continually epidemic in recent years in Guangdong, which raised the concern whether dengue infection is endemic in Guangdong. In this study, we performed phylogenetic, recombinant, and nucleotide variation analyses of 114 complete genome sequences of dengue virus serotypes 1-4 (DENV1-4) collected from 2013 to 2017 in 18 of 21 cities of Guangdong. Phylogenetic analyses revealed that DENV sequences did not form a single cluster, indicating that dengue fever was not endemic in Guangdong, although DENV1-4 co-circulated in Guangdong. Twenty intra-serotype recombinant isolates involving DENV1-4 were detected, but no inter-serotype recombinant events were identified in this study. Additionally, the most recombinant events were detected simultaneously in the gene NS3 of DENV1-4. Nucleotide variation analyses showed that no significant intra-serotype differences were observed, whereas more significant inter-subtype differences were discovered in non-structural genes than in structural genes. Our investigation will facilitate the understanding of the current prevalent status of dengue fever in Guangdong and contribute to designing more effective preventive and control strategies for dengue infection.